Linking Esports to health risks and benefits: Current knowledge and future research needs - Yin, K.; Zi, Y.; Zhuang, W.; Gao, Y.; Tong, Y.; Liu, Y. (Journal of Sport and Health Science, 2020)
Playing and competing in Esports games have significant ramifications for the players` health. With the popularity of Esports continuing to grow rapidly worldwide, research that focuses on understanding the health risks and benefits associated with Esports competition and participation has lagged. Insufficient attention has been given to the development and evaluation of preventive interventions that address the harms that video games associated with Esports may entail. Similarly, gaps exist in our knowledge of ways to promote safe and healthy digital gaming among an ever-growing population of younger Esports athletes. These gaps need to be filled through systematic scientific research so that evidence-based guidelines and intervention strategies, involving healthy diet, regular exercise, and sleep hygiene, can be developed. It is a public health approach that moves toward better integration of Esports gaming and Esports fitness.